Strategic management in the German brewing industry: Are there still differences between East and West - Matthias Heyder; Ludwig Theuvsen (Journal for East European Management Studies, 2008)
Despite the reunification of Germany more than 15 years ago, substantial differences remain between the regions that once comprised the market-driven West and the socialist, centrally planned East. Although today's Eastern German economy is less competitive than the Western German economy, there are important exceptions to the rule. One exception is the food and beverage industry in which Eastern German companies have gained strong competitive positions. Did they reach this position by mimicking Western German blueprints, or did they go their own way? These questions are addressed in this paper by referring to a large-scale empirical study in the German brewing sector. – – Auch mehr als 15 Jahre nach der deutschen Wiedervereinigung sind erhebliche strukturelle und wirtschaftliche Disparitäten zwischen West- und Ostdeutschland feststellbar. Obwohl die ostdeutsche Wirtschaft weniger wettbewerbsfähig ist als die westdeutsche, haben sich einzelne Wirtschaftsbereiche in den neuen Bundesländern dennoch sehr dynamisch entwickelt, z.B. das produzierende Ernährungsgewerbe. In dieser Branche haben sich ostdeutsche Unternehmen erfolgreich im Wettbewerb positioniert. Offen ist, ob sie dies im Wesentlichen durch das Kopieren erprobter westdeutscher Managementkonzepte vermochten, oder ob sie einen eigenständigen Weg beschritten haben. Diese Fragen werden unter Rückgriff auf die Ergebnisse einer Vollerhebung in der deutschen Brauwirtschaft beantwortet.
Keywords: 650; Brewing industry; Eastern Germany; food industry; strategic management; transformation processes transition